Epistemologi Hadis Perspektif Syi’ah - Alfani, Mukhammad; Rochmawati, Ida (Afkaruna: International Journal of Islamic Studies (AIJIS), 2023)
Hadith epistemology is an important part of hadith science, which deals with the methodology of hadith collection, verification, and interpretation. The Shia view of hadith epistemology presents a unique perspective on the sources of hadith and their use in understanding religion and daily life. One of the main differences between Shia and Sunni in the epistemology of hadith is the emphasis on the authority of the Imam in explaining and understanding the meaning of hadith. According to Shia, the Imam is the inheritor of Prophet Muhammad's knowledge and has the authority to interpret the traditions correctly. Therefore, in Shia hadith epistemology, the Imam's authority is essential for understanding the meaning of the hadith. Shia also emphasize the role of reason and correlation in understanding hadith. Shia believe that reason is an important source of knowledge and should be used in the interpretation of traditions. Hence Shias reject the literal approach in understanding traditions and believe that traditions should be understood in their historical and social context. The Shi'a view on the epistemology of hadith is tolerant of differences of opinion in the interpretation of hadith. Shias believe that everyone has the right to interpret hadith according to their own understanding, as long as it does not contradict the basic principles of Islam. As a result, Shia hadith epistemology takes a different view on the sources of hadith and the use of hadith for understanding religion and daily life. Emphasis on the authority of the imam, the role of reason and rationality, and tolerance for differences of opinion characterize Shia hadith epistemology.